Impact of SARS-CoV-2 mRNA vaccine on arthritis condition in rheumatoid arthritis - Takatani, Ayuko; Iwamoto, Naoki; Koto, Serina; Aramaki, Toshiyuki; Terada, Kaoru; Ueki, Yukitaka; Kawakami, Atsushi; Eguchi, Katsumi (Frontiers in Immunology, 2023)
The SARS-CoV-2 mRNA vaccine has been reported to cause various adverse reactions, including the development or exacerbation of autoimmune diseases, but the adverse reactions and the effects of the vaccines on disease activity in patients with rheumatoid arthritis (RA) remain unknown. We therefore investigated the arthritis condition in RA patients after SARS-CoV-2 vaccination.Methods: RA patients who visited our hospital from January to April 2022 completed a questionnaire regarding adverse reactions to the SARS-CoV-2 vaccine. We compared the frequency and duration of post-vaccination arthralgia between RA patients and health care workers in our hospital. For the RA patients who reported post-vaccination arthralgia, we collected medical records for the 6 months after vaccination.Results: Of the 1198 vaccinated RA patients, 256 (21.4%) had systemic inflammatory symptoms, 18 (1.5%) had allergies including urticaria and asthma, and 37 (3.1%) had arthralgia. A few patients had extra-articular manifestations such as acute exacerbation of interstitial lung disease.Compared with health care workers, RA patients more frequently developed arthralgia, and the arthralgia was longer lasting than that in controls: only 9 (0.8%) of the 1117 health care workers reported arthralgia, and all cases resolved within 3 days. Data from 31 of the 37 RA patients with post-vaccination arthralgia were further analyzed; in these patients, disease activity was highest after 2 months, and 10 patients required additional DMARDs within 6 months. The proportion of concomitant use of PSL at vaccination was higher in these patients. No patients on biological DMARDs or targeted synthetic DMARDs prior to vaccination needed additional DMARDs or a change of regimen.RA patients had more frequent and longer-lasting arthralgia after vaccination than healthy subjects, and one-third of patients with post-vaccination arthralgia required additional DMARDs. Although the SARS-CoV-2 mRNA vaccine was administered safely in most RA patients, in some patients RA symptoms may worsen after vaccination.